A risk assessment of salmonellosis linked to chicken meals prepared in households of China. (September 2017) - Zhu, Jianghui; Bai, Yao; Wang, Yeru; Song, Xiaoyu; Cui, Shenghui; Xu, Haibin; Jiao, Xinan; Li, Fengqin
Abstract: A quantitative microbiological risk assessment model was used to quantify the risk of salmonellosis caused by bacterial growth and cross-contamination of chicken meals prepared in households of China. Chinese data on initial loads of Salmonella in chicken carcasses sold at retail, storage time and handling of raw chicken meat in household kitchens and confirmatory transfer rates of Salmonella among different kitchen objects were collected. Only one third of Chinese families in our sample separated the cutting board between raw and ready-to-eat foods. The cross-contamination of ready-to-eat foods from chicken meals via the cutting board, the knife and cooks' hands increased the frequency of pathogen ingestion and the risk of salmonellosis. A significant decrease in the risk of salmonellosis could be achieved by reducing the cross-contamination when handling raw chicken meat and ready-to-eat foods. Decreasing the prevalence of Salmonella contamination to 8.8% or removing chicken carcasses with contamination densities higher than 100 MPN/100 g at retail was less effective. Using transfer rates of Salmonella from raw chicken meat to the wooden cutting board instead of that from references, a statistically higher risk of salmonellosis per serve due to the cross-contamination in households was observed. The present study validated values of hygiene practices in China to reduce the risk of salmonellosis from contaminated raw chicken meat at retail. Deliberate surveys for cooking behaviors and transfer rates of Salmonella from and to different objects including wooden cutting boards were needed. Highlights: Cross-contamination was quantitatively assessed for chicken meals in households of China at first time. Only 1/3 of Chinese families separated the cutting board between raw and cooked foods. Hygienic practices in households prioritized in reducing the risk of salmonellosis. Control prevalence and density of Salmonella contamination at retail is inefficient in reducing risks. Cutting board, particular the wooden board had a leading role in cross-contamination in households.